2016
DOI: 10.17576/jkmjc-2016-3201-12
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y’s Political Participation and Social Media in Malaysia

Abstract: This paper attempts to study the role of Generation Y in expressing their problems, engaging the government through the media especially the social media, and in deciding and voicing their views in the ballot box during the 2008 and 2013 general elections. Generation Y has utilized the social media after the traditional media, like the print and broadcasting media, give them limited space for them to engage with the government and the oppositions Therefore, a survey had been conducted in studying the perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…While the parents of half of the youth join village-level organisations, they are not members of organisations once they leave college or university. Organisation membership is a vital non-political space that has been found to mobilise the youth to participate in protests and petition signing (Bastedo 2015;Jeong 2013) and is a platform for sharing of political news (Shiratuddin et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the parents of half of the youth join village-level organisations, they are not members of organisations once they leave college or university. Organisation membership is a vital non-political space that has been found to mobilise the youth to participate in protests and petition signing (Bastedo 2015;Jeong 2013) and is a platform for sharing of political news (Shiratuddin et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, during the election campaigns, the nature of news sharing changes and the content becomes political. Researchers like Shiratuddin et al (2016) have reported that Malaysian youth share political news via social media. The youth in this study are frequent users of the internet, confirming the Malaysia Youth Index Score 2015 which shows that the youth spend 5-6 hours daily on their mobile phone and 3-4 hours per day surfing the Internet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagi tujuan penambahan peluang pendapatan, media sosial dan aplikasi atas talian tidak pernah meletakkan had dan limitasi dalam pengguna yang ingin menjalankan perniagaan atau pemasaran. Semua golongan dan lapisan masyarakat boleh dan bebas menggunakan media sosial Shiratuddin et al (2016) untuk menambahkan pendapatan mereka. Walaubagaimanapun, etika dan tatacara berhemah semasa menggunakan media sosial perlu dipatuhi bagi mengelakkan masalah dan kesilapan semasa berinteraksi atas talian.…”
Section: Keberkesanan Media Sosial Dalam Menjana Sumber Pendapatanunclassified
“…As suggested by Zainon et al (2017), there is a declining trend of youth political participation in Malaysia; hence, there is a need to further investigate youth participation by looking beyond the factors such as social media usage (SMU). To date, research that has been conducted in Malaysian context mainly focused on the general impacts of SMU by the younger generation such as political campaign, election process and electoral turnout (Salman et al, 2017;Shiratuddin et al, 2016;Zainon et al, 2017). These studies however, have not clearly examined youth behavior and motivation towards online political participation (OPP).…”
Section: Introductionmentioning
confidence: 99%